The Rise of Digital Currencies : Implications for Global Trade and Finance - Abdul Rahman Khan; Zainab Khan; Ahmad Zia Massoud (Proceeding of The International Conference on Economics and Business, 2024)
Digital currencies, including cryptocurrencies and central bank digital currencies (CBDCs), are reshaping global trade and finance. This paper explores their implications for cross-border transactions, financial inclusion, and monetary policy. A comparative analysis of CBDC pilots in Asia and Europe is also presented.